2022
DOI: 10.48550/arxiv.2201.00955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Properties of Type Ibn Supernovae: Implications for the Progenitor Evolution and the Origin of a Population of Rapid Transients

Keiichi Maeda,
Takashi J. Moriya

Abstract: Type Ibn Supernovae (SNe Ibn) show signatures of strong interaction between the SN ejecta and hydrogen-poor circumstellar matter (CSM). Deriving the ejecta and CSM properties of SNe Ibn provides a great opportunity to study the final evolution of massive stars. In the present work, we present a light curve (LC) model for the ejecta-CSM interaction, taking into account the processes in which the high-energy photons originally created at the forward and reverse shocks are converted to the observed emission in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 97 publications
(175 reference statements)
3
10
0
Order By: Relevance
“…A direct comparison of SNe Ibn with SNe Ib is not possible because of the difference in the luminosity powering mechanism. We see, however, that even though the obtained 56 Ni masses are lower than the canonical SESNe (Maeda & Moriya 2022), the ejecta masses obtained are consistent with many SNe Ib as deciphered from the statistical analysis of Lyman et al (2016); Prentice et al (2016). This is also seen in the histograms (Figure 5) that compares SNe 2019uo and 2019wep with the statistical sample of SNe Ib taken from Prentice et al (2019) and Taddia et al (2018).…”
Section: Photometric Evolution Of Sn 2019wepsupporting
confidence: 68%
See 1 more Smart Citation
“…A direct comparison of SNe Ibn with SNe Ib is not possible because of the difference in the luminosity powering mechanism. We see, however, that even though the obtained 56 Ni masses are lower than the canonical SESNe (Maeda & Moriya 2022), the ejecta masses obtained are consistent with many SNe Ib as deciphered from the statistical analysis of Lyman et al (2016); Prentice et al (2016). This is also seen in the histograms (Figure 5) that compares SNe 2019uo and 2019wep with the statistical sample of SNe Ib taken from Prentice et al (2019) and Taddia et al (2018).…”
Section: Photometric Evolution Of Sn 2019wepsupporting
confidence: 68%
“…Fast transients are the group of objects that rise and fade in brightness on timescales much shorter than those of other SNe (Drout et al 2014;Arcavi et al 2016;Pellegrino et al 2021;Maeda & Moriya 2022). Their progenitor systems are uncertain and they have a featureless blue continuum similar to most SNe Ibn.…”
Section: Photometric Evolution Of Sn 2019wepmentioning
confidence: 99%
“…The progenitors of some of these SNe are considered to be massive Wolf-Rayet (WR) stars that shed their outer H and helium (He) layers through strong winds (Crowther 2007), which may constitute the necessitated dense CSM. Recently, Maeda & Moriya (2022) recently found that the CSM density distribution in SNe of type Ibn can be ρ ∝ r −3 , as implied by FBOT radio lightcurves. While the spectrum of such SNe (e.g., type Ibn) is characterized by narrow emission lines, in contrast with that found in FBOTs, some of these WR stars could support the launching of relativistic γ-ray burst (GRB) jets, and give rise to broad emission lines.…”
Section: Introductionmentioning
confidence: 83%
“…the optical properties from LFBOTs (e.g., extremely luminous; too fast rising and decaying to be powered by 56 Ni decay; evidence for H-depleted CSM interaction) and the rare class of luminous stripped envelope stellar explosions which also exhibit evidence for strong CSM interaction−Type Ibn (e.g., Foley et al 2007;Immler et al 2008;Pastorello et al 2015;Hosseinzadeh et al 2017;Pellegrino et al 2022;Maeda & Moriya 2022) and Type Icn SNe (Gal-Yam et al 2022;.…”
Section: Connecting Lfbots To Type Ibn/icn Sne and Other Related Tran...mentioning
confidence: 99%